Sustainable Livelihood Asset-Based Strategy for Rosella Farmers in Pagung Village, Semen District, Kediri Regency - Ratna Putra, Demmy Filsafa; Budi Setiawan; Dwi Retno Andriani (HABITAT, 2022)
Rosella commodity prices, in the range of 15,000 to 30,000, are still relatively low and unstable. Therefore, it is a factor of low motivation in rosella farming. On the other hand, rosella as an annual crop with one big harvest certainly has an impact on farmers' income. The research approach used is a quantitative approach. In this study, livelihood strategies are based on asset characteristics that can be accessed by farmers using 43 respondents and livelihood vulnerability index (LVI) analysis and descriptive analysis. Based on the findings, it showed that the characteristics of the asset that is the lowest accessed and the highest level of vulnerability by rosella farmers is social Asset due to the dependence on meeting their daily needs from government assistance. The results of the study showed that the consolidation strategy was the most appropriate strategy in the context of sustainable livelihoods for rosella farmers through the use of yards to raise cattle or goats. The choice of strategy is based on the lack of access to social Asset for farmers' livelihoods. Where, by raising livestock, farmers can earn additional income outside of rosella farming.